Digital processing : optical transmission and coherent receiving techniques - Binh, Le Nguyen (Optics and photonics (Boca Raton, Fla.), 2014)
"This book describes modern coherent receiving techniques for optical transmission and aspects of modern digital optical communications in the most basic lines. The chapters provide a fundamental understanding of advanced receiving techniques for transport in the optical and electric domains of multi-gigabits per second by coherent mixing in the optical domain, and then processing in the digital domain at the sampling speed of an extremely high rate. The book also includes simplified descriptions of modulation techniques for such digital transmission systems carried by light waves. It discusses the basic aspects of modern digital optical communications in the most basic lines. In addition, the book covers digital processing techniques and basic algorithms to compensate for impairments and carrier recovery, as well as noise models, analysis, and impact on transmission system performance"--